Um programa de treinamento de habilidades de transcrição rítmica - Leme Junior, Antonio Carlos (2023)
Music notation is a code that represents, among other parameters, the frequencies and lengths of musical sounds. It is vital for the musician to be able to distinguish these features of auditory inputs as well as the graphic signals that represent them in order to become proficient at creating and reading a musical score. In an effort to aid in this learning process, the current study suggests a training program for writing in rhythm. An online educational procedure was created for this purpose: over 24 trials, participants were asked to compose the musical stimulus they had heard by selecting and combining three graphic units (rhythmic cells). Eight of these trials (stage 2) were meant to teach each rhythmic cell's sound-visual relation., and the following 16 (stage 3), combinations og these cells. The participants were split into two groups: group A (n=37), where they were given a musical model and instructed to select the visual elements that would make up their writing, and group B (n=39), where between listening and responding, it was requested the observing response of tapping the keyboard in time with the melody. The size effect of the difference between the groups using Cohen's d coeficiente was 0.7 for step 2 (teaching minimal units) and 1.0 for step 3 of the musical writing teaching approach, which indicate the relevance of the observing response in the process. The current study, in our opinion, can advance the discipline of music education and highlights the potential computerized teaching software holds for it.